Overview of the Level of Knowledge About Risk Factors for Coronary Heart Disease in Students in Grades VIII-2 SMP Negeri 1 Pancur Batu - Irfan Sazali Nasution; Dilla Ramadhani; Zahara Ramadani; Sari Nur Lyza; Putri Suci Ramadhani Sirait; Della Putri; Widia Indah Utami; Sukma Ramadini (Universitas Muhammadiyah Palu, 2026)
Coronary heart disease is a type of non-communicable disease and is one of the diseases that need to be considered. can be influenced by an unhealthy lifestyle from adolescence. This study aims to uncover students' understanding of factors that can increase the risk of coronary heart disease at SMP Negeri 1 Pancur Batu. This study uses a quantitative method with a descriptive design and a cross-sectional approach. The research sample amounted to 25 students in grades VIII-2 who were selected using the total sampling technique. Data collection was carried out using a questionnaire containing 15 questions about risk factors for coronary heart disease. The results showed that the majority of respondents were at the level of knowledge in the good category, which reached 16 students (64%), while the sufficient category included 7 students (28%), and the category lacked 2 students (8%). However, risky behaviors such as lack of exercise, consumption of fast food, late sleep, and excessive use of gadgets were still found. The conclusion of this study shows that the level of students' knowledge about the factors that increase the likelihood of coronary heart disease is considered adequate, but a healthy lifestyle still needs to be improved by providing health education from an early age.